2016
DOI: 10.1007/s12010-016-2032-9
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling Activity of Lipidic Metabolites Derived from Padina tetrastromatica

Abstract: An attempt has been made to identify the potential seaweed for antifouling property due to the growing need for environmentally safe antifouling systems. The antibacterial, antimicroalgal, and antimussel foot adherence potentials of methanol, dichloromethane, and hexane extracts of the chosen seaweeds such as Padina tetrastromatica, Caulerpa taxifolia, and Amphiroa fragilissima have been compared against copper sulfate. Among the extracts, the maximum antibacterial activities were exhibited by the methanol ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The MIC of the ethyl acetate extract of the body wall was found to be 0.062 mg/mL against C. muelleri. In a study published in 2016 [6] Suresh et al reported that three marine diatoms tested (P. elongatum, T. frauenfeldii and N. longa) showed high sensitivity to Padina tetrastromatica extract with a MIC of 0.001 mg/mL. The results of the present study also showed that all of the twelve extracts had higher inhibitory activity against C. muelleri compared to C. vulgaris.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The MIC of the ethyl acetate extract of the body wall was found to be 0.062 mg/mL against C. muelleri. In a study published in 2016 [6] Suresh et al reported that three marine diatoms tested (P. elongatum, T. frauenfeldii and N. longa) showed high sensitivity to Padina tetrastromatica extract with a MIC of 0.001 mg/mL. The results of the present study also showed that all of the twelve extracts had higher inhibitory activity against C. muelleri compared to C. vulgaris.…”
Section: Discussionsupporting
confidence: 73%
“…The concentrations were obtained by serial dilution. Then, the tubes were incubated under a controlled condition at 25 °C with the illumination of 4000-5000 lx light intensity [6] with a 12:12 h light/dark cycle. Untreated tube and those containing DMSO served as controls.…”
Section: Determination Of Mic For Microalgaementioning
confidence: 99%
See 3 more Smart Citations